Correction: Brugia malayi Asparaginyl-tRNA Synthetase Stimulates Endothelial Cell Proliferation, Vasodilation and Angiogenesis. - Jeeva Jothi D; Muthu Dhanraj; Shanmugam Solaiappan; Sanjana Sivanesan; Michael Kron; Anuradha Dhanasekaran (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0146132.].